Dramaturgy: Imaging Prabowo Subianto on Twitter as 2024 Presidential Candidate - Zein, Khairani (Jurusan Ilmu Komunikasi UTM, 2023)
Along with its popularity, social media has become an effective tool in political campaigns in many countries. Presidential candidates and their campaign teams use social media to build a desirable image, expand the reach of political messages, rally support, and mobilize voters. There are many ways people can get political messages directly to potential voters on Twitter. This research was conducted using a type of qualitative research with content analysis methods in looking at tweet text related to Prabowo Subianto. And aims to examine the impression management made by Prabowo as a candidate for the 2024 Presidential candidate on the front stage and back stage. The theory used in this study is the Dramaturgy by Erving Goffman, where this article tries to analyze the narrative used in the social media campaign of presidential candidates will also be a key element in building political dramaturgy carried out by Prabowo Subianto as a candidate for the Indonesian presidential candidate through his Twitter account @Prabowo. From the results of the analysis, it can be seen that Prabowo carried out imaging with the aim of trying to convey a convincing, relevant, and interesting narrative for voters, in the hope of building trust and support.